2018
DOI: 10.1002/jcp.27953
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of UCA1 and ITGA2in pancreatic cancer cells target the expression of miR‐107 through focal adhesion pathway

Abstract: Objectives Abnormal expressions of microRNAs (miRNAs) are demonstrated in pancreatic cancer (PaC), but a major part of the mechanism remains elusive. This study mainly aimed to structure a coexpressed network of long noncoding RNA (lncRNA) and messenger RNA (mRNA) in PaC, as well as to explore their direct targets. Methods LncRNA and mRNA microarrays were used to determine the expression profiles in PaC cells. Analysis of Kyoto Encyclopedia of Genes and Genomes pathway was performed to identify pathways associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 32 publications
1
32
0
Order By: Relevance
“…The Long non-coding RNA UCA1 was located in chromosome 9p13.12, and has been found to be overexpressed in tumor tissues, such as esophageal squamous cell carcinoma,colorectal cancer, ovarian cancer, bile duct carcinoma and melanoma etc. [16][17][18][19][20][21][22][23].UCA1 are participated in the tumorigenesis and progression, functioning as an oncogene [24][25][26][27][28][29][30]. However, the relation between UCA1 and renal cancer is still unknown and mysterious particularly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Long non-coding RNA UCA1 was located in chromosome 9p13.12, and has been found to be overexpressed in tumor tissues, such as esophageal squamous cell carcinoma,colorectal cancer, ovarian cancer, bile duct carcinoma and melanoma etc. [16][17][18][19][20][21][22][23].UCA1 are participated in the tumorigenesis and progression, functioning as an oncogene [24][25][26][27][28][29][30]. However, the relation between UCA1 and renal cancer is still unknown and mysterious particularly.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidences suggested that long non-coding RNAs (lncRNAs) perform important or vital functions in the malignant tumors [9][10][11][12][13][14][15]. LncRNA urothelial cancer associated 1 (UCA1) is abnormally expressed in esophageal squamous cell carcinoma, colorectal cancer, gastric cancer melanoma cells, pancreatic cancer, thyroid cancer, lung cancer and so on [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. In vitro and in vivo assays were conducted to further explore its underlying roles in tumor progression.…”
Section: Introductionmentioning
confidence: 99%
“…29,30 The expression of lncRNA UCA1 has been reported to be upregulated in many cancers, including breast cancer, 21,22 colorectal cancer, 31 hepatocellular carcinoma 32 and GC. 33,34 Interestingly, lncRNA UCA1 was found to be participating in cell cycle by targeting mRNA CCNE1 and CDK1 through miR-107 as well. Although this pathway has not been elucidated until now, the inhibition of UCA1 suppressed migration and invasion ability of the cancer cells through a regulatory network of UCA1-miR-107-ITGA2 in pancreatic cancer has been confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic cancer is a highly aggressive malignant tumor with the characteristic of hepatic metastasis [73]. UCA1 promoted migration of pancreatic cancer by sponging miR-107 targeting integrin subunit a 2 (ITGA2) [74]. Moreover, UCA1 could promote pancreatic cancer cell multiplication and metastatic ability by down-regulating miR-96 and up-regulating forkhead box O3 (FOXO3).…”
Section: Pancreatic Cancermentioning
confidence: 99%